The Influence of Organizational Culture and Work Discipline on Employee Performance Through Organizational Support Among Educational and Technical Staff at Universitas Wahid Hasyim - Purwanggono, Cuk Jaka (Universitas KH. Abdul Chalim Mojokerto, 2024)
Human resources management encompasses all individuals involved in organizational activities, ranging from employees to managers and leaders. These individuals not only contribute physical labor but also provide valuable input in the form of thoughts, creativity, and innovation crucial for the progress and success of the organization. A strong organizational culture and high discipline can have a positive impact on organizational activities. Additionally, organizational support is essential in managing human resources to provide motivation and encouragement for the advancement of both employees and the organization. This research method employs statistical analysis using path analysis. The sample consists of 40 respondents. The research findings reveal that organizational culture and work discipline have a significant direct influence on employee performance, while the indirect influence through organizational support is not statistically proven.